Components of teaching English vocabulary in Aviation universities and colleges (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2018)
This paper explores English vocabulary teaching in aviation higher educational establishments, namely tries to define components of teaching vocabulary to aviation students. The starting point of the study is to provide theoretical background and define basic conceptual ideas. Herein, the authors underline the necessity of explicit vocabulary instruction and systematic regular planned work on expanding students’ vocabulary. However, implicit learning while reading and listening is stated to be no less important. Thus, the authors come to the conclusion that both sides of the process should be combined into an effective method of teaching vocabulary. Within this viewpoint four components of teaching English vocabulary to aviation students are defined. Explicit teaching individual words is distinguished to be the first component. It involves teachers’ direct vocabulary instruction as for specifically chosen lexical items. It turns to have best possible results when lexical units are connected with key concepts of the lesson or are the ones used in general language. Providing rich language experience is the second component which deals with students’ vocabulary expansion while reading, listening and speaking. The teacher’s role lies in working out activities aimed at effective vocabulary learning while reading as well as just reading aloud and discussions. The third component, teaching word-learning strategies, is aimed at teaching students to learn words themselves. It includes morphemic analysis, exploring the context and using dictionaries while learning new words. Fostering word consciousness, i.e. awareness of and interest in words, is a significant element in vocabulary teaching providing background for further words learning. It covers word games, tongue twisters, jokes, emphasizing interesting words, etc.
Keywords: explicit teaching; incidental learning; component; vocabulary instruction; word-learning strategy; word consciousness